Improvement of an optimal bus scheduling model based on transit smart card data in Seoul - Nam, Kihwan; Park, Myungkeun (Transport, 2018)
This study was initiated with a goal of improving the bus scheduling model using the past data of “smart card”. Traffic congestion level of Seoul is keep aggravating and it also has negative influence on air pollution and our health. Additionally, this heavy traffic causes high congestion costs. The continuous quantitative growth of the public transportation system brings the necessity of its efficient operation system for its future qualitative growth. The improvement of operation system is necessary also to improve public transportation operation cost efficiency of Seoul. In other words, the systematic planning is necessary for maximizing passengers’ satisfaction level and the public transportation operation cost efficiency of Seoul. The current allocation interval of Seoul bus system is designed based on the empirical data of the past, which is incapable of immediate response to rapidly changing passenger demands. This research analyses passengers’ behaviour and makes a proposal for the traffic network operation by analysing the “traffic card (smart card) big data”, which comes from over 90% of the passengers so as to be flexible in dealing with rapid changes in demand.